2018
DOI: 10.1371/journal.pone.0206796
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of antiretroviral therapy: Incidences, patterns and risk factors of opportunistic infections in an urban Ugandan cohort

Abstract: BackgroundDespite increased antiretroviral therapy (ART) coverage and the raised CD4 threshold for starting ART, opportunistic infections (OIs) are still one of the leading causes of death in sub-Saharan Africa. There are few studies from resource-limited settings on long-term reporting of OIs other than tuberculosis.MethodsPatients starting ART between April 2004 and April 2005 were enrolled and followed-up for 10 years in Kampala, Uganda. We report incidences, patterns and risk factors using Cox proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 55 publications
8
28
4
1
Order By: Relevance
“…HIV-infected children with CD4 count or % below the threshold at the time of ART initiation were more likely to develop OIs as compared to those children with CD4 counts or % above the threshold). A 10 year retrospective study conducted in Uganda [40] documented that the occurrence of OIs in patients with lower CD4 cell counts at ART start was significantly high. Similar studies conducted in India [32,36], Latin America [29,30,41], and Asia [21] showed that low CD4 counts during ART enrollment significantly increased the risk of developing OIs.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-infected children with CD4 count or % below the threshold at the time of ART initiation were more likely to develop OIs as compared to those children with CD4 counts or % above the threshold). A 10 year retrospective study conducted in Uganda [40] documented that the occurrence of OIs in patients with lower CD4 cell counts at ART start was significantly high. Similar studies conducted in India [32,36], Latin America [29,30,41], and Asia [21] showed that low CD4 counts during ART enrollment significantly increased the risk of developing OIs.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models with T-cell deficiencies, NK cells conferred protection against Mtb infection [ 16 ]. Therefore persistent NK cell activation and dysfunction observed among ART-treated adults in sub-Saharan Africa, where Mycobacterium tuberculosis infection is endemic, presents a potential mechanism for the persistently high levels of active tuberculosis in our HIV treatment cohort [ 20 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete recovery of NK cell repertoire could contribute to the persistent T-cell function abnormalities previously described in our cohort of ART-treated adults, even when CD4 counts were restored to levels above 500 cells/μl [ 18 ]. With emerging evidence that NK cell function is key to protection against progression from latent Mtb infections to active tuberculosis, understanding recovery of NK cell function during ART is essential to the control of Mtb infection among ART-treated HIV-infected adults in sub-Saharan Africa where Tb remains a leading opportunistic infection and a leading cause of death [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Successful roll-out of antiretroviral therapy (ART) has significantly reduced morbidity, mortality and incidence of opportunistic infections associated with Human Immunodeficiency Virus (HIV) infection and acquired immune deficiency syndrome. [ 1 ] However, Sub-Saharan Africa continues to be disproportionately burdened by the HIV-1 epidemic and the region has the greatest number of deaths, morbidity, and opportunistic infections. [ 2 ] One of the major biological barriers to complete eradication of HIV-1 is the ability of the virus to compartmentalise in reservoir sites such as the central nervous system (CNS), lymphoid tissue, gut tissues, and other anatomical sites.…”
Section: Introductionmentioning
confidence: 99%